Desarrollo de un sistema experto para la planificación y verificación de evaluaciones en el área de riesgos del trabajo del Instituto Ecuatoriano de Seguridad Social Loja. - Carrillo Martínez, María Cristina (2014)
The graduation work had the “development and implementation of an expert system for planning and verification reviews in the labor risk area in Loja IESS “, since planning is the most important administrative functions, it could say that it is the process through a vision of the future is got, where it is possible to determine and achieve the goals through the choose of a course of action. On the other hand for job evaluations to a work team it aims to reach the objective decision on human resources. Modern organizations use evaluation of worker to determine salary increases, training and development needs, as well as provide documentation to support the actions of staff turnover. As a result, a well-managed evaluation serves as instrument of supervision and staff development. Verification of assessments , become a process to stimulate or judge the value , excellence and the qualities of the performance of a server , it is a management tool , essential in the administrative activity , helps determine policies adequate human resource the needs of the organization. For the development of the following software tools are used Java as development language using the Netbeans IDE platform manager as the MySQL database was used, plus the Weka libraries for developing the inference engine was used planning schedule module and the Swi- Prolog ( jpl.jar ) Seller as inference engine to calculate the evaluation results For the testing process JUNIT tool in order to verify, manage and execute automated test set was used.